A cross sectional study of knowledge, attitude and practices regarding menstrual hygiene among ashram school adolescent girls in field practice area of tertiary health care hospital in Navi Mumbai - Gosavi, Jayesh; Velankar, Deepa H.; Joshi, Sumedha; Wasnik, Sumit; Ramaswamy, Sudarshan (International Journal Of Community Medicine And Public Health, 2021)
Background: Adolescent girls often lack knowledge regarding menstruation which may be associated with taboos and myths existing in our traditional society which has a negative implication for women’s health, particularly their menstrual hygiene. Aim of the current study is to investigate existing knowledge, attitude and practices regarding menstruation and to assess the source of information, beliefs, misconceptions and restrictions related to menstruation among adolescent school girls. Methods: The study was undertaken among all adolescent girls of 7th to 10th standard of ashram school in September 2018 to Oct 2018 by pre-designed, close ended questionnaire and the data was analysed. Results: Out of the 100 girls who had attained menarche, all participants used sanitary pads as it was provided by school. Maximum girls had positive attitude towards menstruation, 58% girls got information about menstruation from their teacher. For cleaning of genitals during menstruation 58% girls used water and soap, 7% used water and antiseptic and 35% used water only. Method of adsorbent disposal was reported as burn (51%) and burial (44%). 42% and 49% of girls were not allowed to do household activities and kitchen work respectively. 95% and 63% of girls weren’t allowed to go to temple and do sport activities respectively. Conclusions: In the study, it was observed that among the adolescent ashram school girls, the knowledge of menstruation was good and the practices were optimal for proper hygiene but superstitious beliefs and taboos affect their day to day activity during menstruation.